SELF INDIVIDUATION PROCESS IN THE MAIN CHARACTER OF BLACK SWAN MOVIE - Suprapto, Yohana Febry Chris (LANTERN (Journal on English Language, Culture and Literature), 2016)
Black Swan movie directed by Darren Aronofsky is a movie which includes many psychological aspects in it. This movie tells us about a journey to find the true self of the main character named Nina Sayers. The writer uses library research in collecting the data. The objectives of this thesis are to describe both intrinsic aspects which include narrative (theme, character, setting and conflict) and cinematic elements (mise-en-scene, camera distance, and sound) and to explain extrinsic aspects. To analyze the extrinsic aspects of the movie, the writer usespsychological approach. The writer analyses how Nina finds her true self related to Carl Jung theory about self individuation process. There are four kinds of archetypes in order to acknowledge the self individuation process. They are “persona”, “shadow”, “anima and animus”, and “Self”. Eventually, the writer finds that Nina does not experience those four archetypes. The result of this thesis is the “shadow” and “persona” are two archetypes which dominate Nina. It can be stated that the main character does not succeed in the process of self individuation proposed by Carl Gustav Jung.